(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The importance of women to national progress is steadily growing. Many women now splittheir time between working at home and in the workplace. It’s a difficulty for any working woman sincethey have to deal with a plethora of issues in their personal lives in addition to the stresses of theworkplace. They struggle to maintain a healthy work-life balance due to the pressures of their jobs.Women’s participation in the workforce has increased dramatically over the last three decades, and nowincludes the armed forces, law enforcement, the medical profession, and even the engineering sector.Shift labor became the norm in many industries, and both men and women participated. The effects onwomen’s lifestyles and the additional stress that comes with working late hours or night shifts are welldocumented.The purpose of the current study is to determine what kinds of pressures are placed onwomen in the ITES industry, particularly those who work late shifts and go home around midnight.Researchers in this study analyzed how working long hours affected the health and happiness of womenin the information technology and business process outsourcing (BPO) sector. The balance betweenwork and family life is greatly affected by a woman’s working hours. Working long hours has asignificant effect on every dependent variable, including family members’ complaints about how littletime women workers spend with them, the frequency with which they engage in conversation with them,the frequency with which they argue with them, and the frequency with which they bond in relationshipwith them.